Reliability of Intraoperative Monitoring in Patients with a Preexisting Motor Deficit: Case Report and Literature Review - Visagan, Ravindran; Lavrador, José Pedro; Acharya, Shami; Pereira, Noemia; Bodi, Istvan; Ashkan, Keyoumars; Bhangoo, Ranjeev; Vergani, F. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background The use of intraoperative monitoring (IOM) in glioma surgery is a widely adopted and clinically validated adjunct to define safe zones of resection for the neurosurgeon. However, the role of IOM in cases of a significant preexisting motor deficit is questionable.Case Description We describe a case of a 25-year-old with a recurrent presentation of a left paracentral glioblastoma, admitted with intratumoral hemorrhage and subsequent acute severe right-sided weakness. The patient underwent a redo left parietal craniotomy and 5-aminolevulinic acid–guided resection with IOM. The severity of the weakness was not reflected by the pre- and intraoperative cortical motor evoked potentials (MEPs) that were reassuring. The patient's hemiparesis recovered to full power postoperatively.Conclusions Preoperative weakness is traditionally accepted as a relative contraindication to IOM and therefore its usefulness is questioned in this context. Our case challenges this assumption. We present the clinical course, review the cranial and spinal literature including the reliability of IOM in cases of preoperative motor deficit, and discuss the need for tailor-made IOM strategies.
Keywords: preoperative motor deficit; intraoperative neuro-monitoring; monopolar stimulation; glioma; surgery